(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2020)
The purpose of the article is to show in outline how in the specific conditions of Poland before 1989 religious inspiration was a significant factor in creating civil society. The author illustrates the importance of religious inspiration mainly by giving examples of initiatives undertaken by Primate Stefan Wyszyński. The author also analyzes various understandings of civicness, indicating the difference in Western and Central European (in particular Polish) perceptions of freedom, community, and civil society. A fundamental difference is noticed in the absence of native traditions of social contract that would exclude the influence of the sacred sphere on civicness.